Concomitant MDS with isolated 5q deletion and MGUS: case report and review of molecular aspects - Nolte, Florian; Mossner, Maximilian; Jann, Johann-Christoph; Nowak, Daniel; Boch, Tobias; Müller, Nadine Zoé; Hofmann, Wolf-Karsten; Metzgeroth, Georgia (European journal of haematology, 2017)
Patients with monoclonal gammopathy of undetermined significance (MGUS) have a higher risk for the development of concomitant primary cancers such as multiple myeloma (MM) and myelodysplastic syndrome (MDS). We report the case of patient initially suffering from MGUS of the IgG lambda subtype for more than 10 yr, which evolved to MM and MDS with deletion (5q) with severe pancytopenia. Due to pancytopenia, he received dose-reduced treatment with lenalidomide and dexamethasone. He achieved an ongoing transfusion independency after about 1 month of treatment. Bone marrow taken 14 months after start of treatment showed a complete cytogenetic response of the del(5q) clone and a plasma cell infiltration below 5%. In contrast to the development of MM in MGUS patients, the subsequent occurrence of MDS after diagnosis of MGUS is infrequent. Moreover, the biological association of MDS with MGUS is not sufficiently understood, but the non-treatment-related occurrence supports the pathogenetic role of pre-existing alterations of stem cells. Here, we summarize data on concomitant MDS and MGUS/MM with particular emphasis on molecular aspects.